A unique B cell epitope-based particulate vaccine shows effective suppression of hepatitis B surface antigen in mice. Issue 2 (29th March 2019) - Zhang, Tian-Ying; Guo, Xue-Ran; Wu, Yang-Tao; Kang, Xiao-Zhen; Zheng, Qing-Bing; Qi, Ruo-Yao; Chen, Bin-Bing; Lan, Ying; Wei, Min; Wang, Shao-Juan; Xiong, Hua-Long; Cao, Jia-Li; et al.
Abstract : Objective: This study aimed to develop a novel therapeutic vaccine based on a unique B cell epitope and investigate its therapeutic potential against chronic hepatitis B (CHB) in animal models. Methods: A series of peptides and carrier proteins were evaluated in HBV-tolerant mice to obtain an optimised therapeutic molecule. The immunogenicity, therapeutic efficacy and mechanism of the candidate were investigated systematically. Results: Among the HBsAg-aa119-125-containing peptides evaluated in this study, HBsAg-aa113-135 (SEQ13) exhibited the most striking therapeutic effects. A novel immunoenhanced virus-like particle carrier (CR-T3) derived from the roundleaf bat HBV core antigen (RBHBcAg) was created and used to display SEQ13, forming candidate molecule CR-T3-SEQ13. Multiple copies of SEQ13 displayed on the surface of this particulate antigen promote the induction of a potent anti-HBs antibody response in mice, rabbits and cynomolgus monkeys. Sera and purified polyclonal IgG from the immunised animals neutralised HBV infection in vitro and mediated efficient HBV/hepatitis B virus surface antigen (HBsAg) clearance in the mice. CR-T3-SEQ13-based vaccination induced long-term suppression of HBsAg and HBV DNA in HBV transgenic mice and eradicated the virus completely in hydrodynamic-based HBV carrier mice. The suppressive effects on HBsAg were strongly correlated with the anti-HBs level after vaccination, suggesting that the main mechanism of CR-T3-SEQ13 vaccination therapy was the induction of a SEQ13-specific antibody response that mediated HBV/HBsAg clearance. Conclusions: The novel particulate protein CR-T3-SEQ13 suppressed HBsAg effectively through induction of a humoural immune response in HBV-tolerant mice. This B cell epitope-based therapeutic vaccine may provide a novel immunotherapeutic agent against chronic HBV infection in humans.